2008
DOI: 10.2174/157488408785747647
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Burn Injury and Vitamin D Metabolism and Consequences for the Patient

Abstract: The stress and inflammatory responses to burn injury are associated with bone loss. The stress response entails production of large amounts of endogenous glucocorticoids that decrease osteoblasts on the mineralization surface of bone and decreases differentiation of marrow stromal cells into osteoblasts, thereby decreasing the amount of bone formation. Deficiency of osteoblasts also blocks osteoclastogenesis thus leading to low bone turnover and bone loss. The inflammatory response generates cytokines such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The low vitamin D levels we detected in our patients did not correlate with sun exposure or age and none of our patients had a BMI ≥40 nor did their BMI correlate with serum vitamin D. PTH serum levels were normal; except for one patient with hypoparathyroidism; indicating proper vitamin D activation. One possible suggestion is that the extent of KC apoptosis in PV may diminish the skin capacity to produce vitamin D in a manner similar to burned patients who cannot synthesize vitamin D normally . Evaluating the impact of extensive KC apoptosis on vitamin D levels may possibly examine the validity of this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low vitamin D levels we detected in our patients did not correlate with sun exposure or age and none of our patients had a BMI ≥40 nor did their BMI correlate with serum vitamin D. PTH serum levels were normal; except for one patient with hypoparathyroidism; indicating proper vitamin D activation. One possible suggestion is that the extent of KC apoptosis in PV may diminish the skin capacity to produce vitamin D in a manner similar to burned patients who cannot synthesize vitamin D normally . Evaluating the impact of extensive KC apoptosis on vitamin D levels may possibly examine the validity of this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible suggestion is that the extent of KC apoptosis in PV may diminish the skin capacity to produce vitamin D in a manner similar to burned patients who cannot synthesize vitamin D normally. 29 Evaluating the impact of extensive KC apoptosis on vitamin D levels may possibly examine the validity of this hypothesis. Interestingly, the dietary vitamin D intake of our patients during their monthly admission (1 week/month) to receive IV pulse steroid therapy was much lower than the recommended daily allowance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, burned skin is not able to manufacture normal quantities of vitamin D3 leading to further derangements in calcium and vitamin D levels. A study of pediatric burn patients found that supplementation with a multivitamin containing 400 IU of vitamin D2 did not correct vitamin D insufficiency [8082]. More investigation into therapies to combat calcium and vitamin D deficiency is needed.…”
Section: Reviewmentioning
confidence: 99%
“…After burn, obese patients may respond with amplified inflammation, increased hypermetabolism, brisker and more severe muscle wasting, and severe insulin resistance [111]. Obese patients also have decreased bioavailability of vitamin D3 compared to non-obese patients which can potentially worsen vitamin D and calcium deficiency after burn in this population [80]. …”
Section: Reviewmentioning
confidence: 99%
“…There are a number of mechanisms by which these patients could become deficient in vitamin D and possibly compounded by deficiency on admission. This results in a deficiency of metabolically active vitamin D. 51,52 A recent review suggests that replenishment of vitamin D levels can be considered in two phases, restoration and maintenance. Furthermore, the use of pressure garments and wound dressings limit the area of skin available for sun exposure and hence vitamin D production.…”
Section: Discussionmentioning
confidence: 99%